STATUS DAN FUNGSI EYANG SERTA PERAN EYANG (GRANDPARENT) MENURUT PANDANGAN DAN SIKAP EYANG DI LINGKUNGAN UNY - Hiryanto Hiryanto (LPPM UNY, 2006)
This research aims to gain data and information about the olds called Eyang (grand parents) viewed from their attitude and view on the status, function, and role as grandparent, as well as their living. The approach of this research is qualitative. Through this approach, deep, authentic, various, and unique information can be gained. The samples taken using purposive sampling are lecturers and staffs in Yogyakarta State University who is considered as eyang. Data collection is done through open-ended questionnaire to gain deep information. The data collected are analyzed using qualitative-descriptive technique. The research result shows that the background of education and the degree of employment do not influence how to be wise, love the grandchildren. However, those factors are related to economical burden of the existence of the grand children. The grandparents realize that they have complex role between the reality and the future. Therefore, they try hard to build harmonic communication in frame of loving the children. There are differences between the role of grandmother and grandfather in loving children. In context of role for future, not all grandparents feel ready. They think they need to learn. High intention of loving children limits them. It needs further study which involves condition or changes that is not covered in this research. It also needs to widen the setting of the research as well as the implementation of the policy in society.